2011
DOI: 10.3109/09593985.2011.574783
|View full text |Cite
|
Sign up to set email alerts
|

Criteria of gait asymmetry in patients with hip osteoarthritis

Abstract: Gait symmetry is often a goal for physiotherapy in patients with hip osteoarthritis and after total hip replacement. However, there is no agreement on criteria for pathological gait asymmetry. In this study we investigated discriminative abilities of trunk and footfall gait symmetry measures, and thereafter assessed whether a 10% cutoff value is valid as a general criterion of pathological gait asymmetry across measures. Anteroposterior, vertical, and mediolateral trunk symmetry, single support, and step lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…Achieving full gait symmetry is often an important target for physiotherapy in people with various diseases and functional anomalies [5,8]. Examples of clinical trials include a comparison between dysfunctional gait and normal people with hypothetical gait symmetry [13].…”
Section: The Effect Of Disease and Anomalies On Gait Symmetrymentioning
confidence: 99%
See 2 more Smart Citations
“…Achieving full gait symmetry is often an important target for physiotherapy in people with various diseases and functional anomalies [5,8]. Examples of clinical trials include a comparison between dysfunctional gait and normal people with hypothetical gait symmetry [13].…”
Section: The Effect Of Disease and Anomalies On Gait Symmetrymentioning
confidence: 99%
“…In this case, gait asymmetry is considered an important factor to evaluate the functional inefficiency of the patients with the anomaly. Thereby, achieving gait symmetry or reducing gait asymmetry in people with any disorder before and after rehabilitation has been used to assess the effectiveness of the treatment model [2][3][4][5][6]. In this context, the results of several studies have also shown the effectiveness of rehabilitation exercises [3,30,39,47].…”
Section: The Effect Of Disease and Anomalies On Gait Symmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…In pathological gait, marked differences have been reported between the affected and unaffected limbs, as observed in amputee gait (Kaufman et al, 2012), in post-stroke patients (Lewek et al, 2014), in hemiplegic subjects, in hemiparetic patients, ageing and Parkinson's disease (Yogev et al, 2007), in patients with limb length inequality (Kaufman et al, 1996), or osteoarthritis and THA patients (Hodt-Billington et al, 2012). These examples illustrate how gait asymmetry can be a direct consequence of abnormality, and, furthermore, can reduce the performance of everyday tasks and the quality of life (Kaufman et al, 2012).…”
Section: Gait Variability and Symmetry Assessment With Inertial Sensomentioning
confidence: 99%
“…Lower-limb gait asymmetry (GA) is characteristic of a number of chronic neurological and mu culo kele al i ea e [1] inclu ing cerebral pal y [2] Parkin on' i ea e [3] an knee and hip osteoarthritis [4][5]. Onset of GA can also follow acute events such as stroke [6] and amputation [7].…”
Section: -Introductionmentioning
confidence: 99%